Peran Peran Orangtua Terhadap Penggunaan Masker Di Masa Pandemi Covid-19 - Monifa Putri; Rizka Angrainy; Rika Istawati (Al Tamimi Kesmas: Jurnal Ilmu Kesehatan Masyarakat (Journal of Public Health Sciences), 2022)
The Covid-19 pandemic which causes death worldwide is a very important health problem to pay attention to. Rapid transmission through the air and in crowded places makes us have to be careful and always apply health protocols, one of which is to wear masks both inside and outside the room. Parents have a role in educating, being role models for children, and reminding children to always maintain personal hygiene, and use masks during the Covid-19 pandemic. Methods: This research is analytic by using a cross-sectional approach. Sampling technique using total sampling. Data analysis was performed using the Chi-Square test at a significance level of p<0.05. Results: The majority of parents contributed to the use of masks 68.8% compared to those who did not use masks 31.2%. While parents who do not play a role in the use of masks 87.5% are more dominant than those who do not use masks by 12.5%. The chi-square statistical test results showed a P < 0.05 (P = 0.000). It can be concluded that there is a relationship between the role of parents and the use of masks, the value of P <0.05 (P = 0.000).